Neimark-Sacker Bifurcation in a Discrete-Time Financial System - Baogui Xin; Tong Chen; Junhai Ma (Discrete Dynamics in Nature and Society)
A discrete-time financial system is proposed by using forward Euler scheme. Based on explicit Neimark-Sacker bifurcation (also called Hopf bifurcation for map) criterion, normal form method and center manifold theory, the system's existence, stability and direction of Neimark-Sacker bifurcation are studied. Numerical simulations are employed to validate the main results of this work. Some comparison of bifurcation between the discrete-time financial system and its continuous-time system is given.